2012
DOI: 10.1371/journal.pone.0041739
|View full text |Cite
|
Sign up to set email alerts
|

Does Pet Arrival Trigger Prosocial Behaviors in Individuals with Autism?

Abstract: Alteration of social interactions especially prosocial behaviors – an important aspect of development – is one of the characteristics of autistic disorders. Numerous strategies or therapies are used to improve communication skills or at least to reduce social impairments. Animal-assisted therapies are used widely but their relevant benefits have never been scientifically evaluated. In the present study, we evaluated the association between the presence or the arrival of pets in families with an individual with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 67 publications
3
59
2
2
Order By: Relevance
“…This questionnaire was previously developed and used [25,28]. Parents were asked about their pet ownership (i.e.…”
Section: [Insert Table 1]mentioning
confidence: 99%
“…This questionnaire was previously developed and used [25,28]. Parents were asked about their pet ownership (i.e.…”
Section: [Insert Table 1]mentioning
confidence: 99%
“…The provision of service animals for autism may provide similar benefits, with parent-reported outcomes including increased safety, independence and socio-emotional functioning 32,33 , and corroborating parent-report and physiological data may indicate decreases in stress 34 . Increases in prosocial behaviours may also be elicited by companion animals 37 . However, despite predominantly positive outcomes, the current literature is limited by small sample sizes, few controls and often non-blind observation and informant reports.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study to date has empirically evaluated the introduction of a companion animal into the home for children with autism. Findings indicated that pet arrival triggered increased prosocial behaviour 37 . However, despite promising findings in this study, companion animals should not be interpreted as substitutes for AAI or as certified service animals for autism.…”
Section: Companion Animalsmentioning
confidence: 99%
“…Many of these benefits may not be related to the specific training that these assistance animals receive, but rather are incidental results of the dog being present. Indeed, Grandgeorge et al (2012) report an increase in pro-social behaviors in children with autism upon acquisition of a pet dog. Parental reports suggest that the presence of an assistance dog in the home results in reduced child anxiety, and this is supported by decreases in cortisol awakening responses in these children following placement of the dog, which increase again following removal of the animal (Viau et al 2010).…”
mentioning
confidence: 99%
“…These wider positive effects on the whole family could potentially lead to better overall family functioning, which could positively impact upon behavioral problems. In point of fact, pets provide a pivotal role in family functioning (Walsh 2009), providing an attachment source which may help bring the family members together (Cain 1983;Kurdek 2008;Grandgeorge et al 2012) and reduce stress and promote interaction between members of the family group (Allen and Blascovich 1996).…”
mentioning
confidence: 99%